VO2 (A)/graphene nanostructure: Stand up to Na ion intercalation/deintercalation for enhanced electrochemical performance as a Na-ion battery cathode. (10th January 2019) - Hu, Xinyuan; Zhao, Zhengjing; Wang, Lin; Li, Jingbo; Wang, Chengzhi; Zhao, Yongjie; Jin, Haibo
Abstract: Intercalation/deintercalation of large size Na ion leads to serious electrode materials fragmentation that would be the main reason of Na-ion battery capacity fading. Herein, we reported a Na-ion battery cathode material composed of layer-structured VO2 (A) nanowires wrapped with graphene. The VO2 (A)/graphene nanostructure which effectively suppressed pulverization of VO2 (A) nanowires during cyclic charging and discharging exhibited prominent cycle stability and high specific capacity. A reversible capacity of 115 mA h g −1 was retained over 100 cycles at a high current density of 100 mA g −1 . Comparing to the electrochemical performance of other vanadium oxides, VO2 (A)/graphene demonstrates a potential cathode material for Na-ion batteries. Highlights: VO2 (A) nanowires and its graphene composites are synthesized easily. VO2 (A)/Gr shows prominent cycle stability and high specific capacity as SIB cathode. Layered structure of VO2 (A) is favorable to intercalation/deintercalation of Na ion. Graphene coating greatly suppresses pulverization and aggregation of VO2 (A).